2010
DOI: 10.1002/cncr.25089
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of systemic therapy for patients with deep fibromatosis (desmoid tumor)

Abstract: BACKGROUND: In the current study, the authors examined the outcomes of patients with desmoid tumors who received systemic therapy at a single institution to provide a basis for the examination of newer agents. METHODS: Records of patients with desmoid tumors who were treated with chemotherapy at the study institution were reviewed. The activity of nonsteroidal anti-inflammatory drugs was not addressed. Patients without measurable disease and those receiving therapy could not be documented, and those receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
118
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(123 citation statements)
references
References 23 publications
1
118
0
4
Order By: Relevance
“…Чаще применяют гормональную и цитостатическую тера-пию. Анализ литературы показал, что имеется до 157 раз-личных комбинаций лекарственного лечения [32,33].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Чаще применяют гормональную и цитостатическую тера-пию. Анализ литературы показал, что имеется до 157 раз-личных комбинаций лекарственного лечения [32,33].…”
Section: Discussionunclassified
“…Чаще применяют в ка-честве первой линии при нерадикальных операциях либо при прогрессировании заболевания [31,[33][34][35][36].…”
Section: Discussionunclassified
“…Based therapy regarding response rates. In the series of de Camargo, anthracyclines in combination with hormonal therapy demonstrated the greatest RECIST response rates (6). Endocrine and/or NSAID therapy is often considered first-line medical treatment for unresectable, advanced disease without clinical symptoms (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no controlled randomized trial in this setting. The influence of chemotherapy in the treatment of the desmoid tumors is unclear and limited (2,7,18,28). However, some retrospective series and the French sarcoma group study demonstrated good outcomes with chemotherapy (29).…”
Section: Discussionmentioning
confidence: 99%